Hybridization and spore dissection of native wine yeasts for improvement of ethanol resistance and osmotolerance - Sanchez, Maria Laura; Chimeno, Selva Valeria; Mercado, Laura Analia; Ciklic, Ivan Francisco (Springer, 2022)
Global warming has a significant impact on different viticultural parameters, including grape maturation. An increment of photosynthetic activity generates a rapid accumulation of sugars in the berry, followed by a dehydration process which leads to a higher concentration of soluble solids. This effect is exacerbated by current viticultural practices which favor the harvest of very mature grapes to obtain wines with sweet tannins. Considering the initial hyperosmotic stress conditions and the high ethanol concentration of the produced wine, fermentation of grape musts with high sugar content could be problematic for yeast starters. In the present study, we were able to obtain by classical hybridization and spore dissection methods one hybrid and one monosporic wine yeast strain with a combined ethanol and osmotolerant phenotype. The improved yeasts were tested in vinification trials with high sugar concentration and displayed excellent fermentation performance. Importantly, the obtained wines also showed good organoleptic properties during sensory analysis. Based on our results, we believed our improved hybrid and monosporic strains can be considered good alternatives to be used as yeast starters for fermentations with high sugar content.